Impact of Tourism Products Development on Osun Osogbo Sacred Grove and Badagry Slave Trade Relics - Oladipo, Oladeji Sunday; Modupe, Olatuyi Funmilayo (Journal of Tourism Management Research, 2020)
Cultural heritage sites are considered as tourism magnates with social, cultural and economic values. Dearth of information on the perception of the visitors and the heritage managers on the impacts of development of tourism products has necessitated this research finding. The two heritage sites considered are of unique cultural values to Nigeria and the World. While Osun Osogbo Sacred Grove is listed on UNESCO Heritage List, Badagry Slave Trade Relics is a National Monument. Multiple research techniques employed in undertaken the study include field observation, questionnaire administration and Key Informant Interview. Total of 293 questionnaire were valid for descriptive analysis while the interview was subjected to thematic analysis. The field observation aids in identification of the tourism products complemented by knowledgeable source. Inferential statistics was used in testing the hypothesis. In-depth information on the tangible and intangible heritage resources into the study areas was revealed and documented. Identified tourism products were listed, categorized and their level of development were appraised. Demographic characteristics of the respondents and their perception on the impacts of tourism products were presented. Chi Square test shows that age, marital status, education, occupation and religion had significant relationship with total perception on tourism products development at P<0.01 and P<0.05. Research outcome will serve as blue print in the quest for appropriate model for sustainable tourism development in heritage sites. Heritage site managers, conservation administrators, tourists and other relevant stakeholders will benefit tremendously in the research output.